Economics and Finance Readings : Asia-Pacific Conference on Economics and Finance, 2023 - Evan, Lau; Widya, Paramita; Tee, Kai Hong; Tan, Lee Ming (Springer Nature Singapore Pte Ltd., 2024)
The Asia Pacific Conference of Economics and Finance (APEF 2023) was held on December 14–15, 2023, at the Holiday Inn Singapore Atrium. Researchers from a wide array of countries, including Cambodia, China, Czechia, Germany, Hong Kong, India, Indonesia, Ireland, Japan, the Netherlands, New Zealand, Polska, Philippines, Singapore, South Africa, Taiwan, U.A.E, UK, and the United States, presented a total of 42 research papers. The conference included keynote presentations from Denise Cheok, Assistant Director at APAC Economist, Moody’s Analytics, Singa-pore, who discussed ‘APAC Outlook: Holding Firm’, and Dr. Kai-Hong Tee from Loughborough University, UK, who presented on ‘Hedge fund inceptions and market competition’. This book presents a curated selection of 14 outstanding papers that were show- cased at APEF 2023, providing readers with profound insights into a wide spectrum of economics and finance topics. Collectively, these papers offer a comprehensive overview of the key challenges and opportunities shaping the economic and financial landscape of the Asia Pacific, making a valuable contribution to the discourse on regional development and policy formulation. APEF 2024 will be held in person on December 12–13, 2024, at the Holiday Inn Singapore Atrium. For more information about the conference, please visit APEF. ear.com.sg. You are warmly invited to participate, and I eagerly anticipate your involvement.